Performing contemporary Indonesia : celebrating identity, constructing community - Hatley, Barbara; Hough, Brett; Murti, Yoshi Fajar Kresno (Southeast Asia mediated., 2015)
"Performance events have long had a central place in Indonesian societies in displaying power, affirming social relations, celebrating shared values, and at times conveying potent political critique. How have they responded to the momentous social and political changes of recent years--the dismantling of the centralised, authoritarian Suharto regime and its replacement with a more open, regionally-focused political system, the rapid expansion of global cultural influence? Investigations of diverse performance genres from different regions illustrate the way general socio-political processes play out locally, and how particular groups are responding. Exploring performed understandings of identity and community, such studies expand knowledge of a complex, contested period of change in Indonesia and the workings of contemporary performance in giving it expression"--